Journal of Ethnobiology and Ethnomedicine - achievements and perspectives - Pieroni Andrea (BMC, 2006)
Abstract Last summer we officially launched the Journal of Ethnobiology and Ethnomedicine, published by BioMedCentral, with the aim of establishing a serious, peer-reviewed, open-access online journal that focuses on the multidisciplinary, interdisciplinary, and transdisciplinary fields of ethnobiology and ethnomedicine, drawing on approaches and methods from both the social and biological sciences. The strong start vindicates the widely held belief that the journal responds to a real need within the research community. The success of the journal has been most gratifying. The steady influx of submissions of high scientific standards illustrates the strong demand for a dynamic, proactive, and open-minded scientific journal in these research areas. Our aim has been to dedicate JEE to the "scientific communities" worldwide, particularly those in the developing countries.